A double-layer stacked antimony-sulfur silver-based gradient film and its preparation method

By adopting a double-layer stacked sulfonyluoroante silver-based gradient film structure in AgSbS2 solar cells, the problem of insufficient short-circuit current and open-circuit voltage of existing AgSbS2 solar cells is solved, and the efficiency is significantly improved.

CN115966618BActive Publication Date: 2025-03-18CHONGQING UNIV OF ARTS & SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211383955.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-07
Publication Date
2025-03-18
Estimated Expiration
2042-11-07

AI Technical Summary

Technical Problem

The short-circuit current of existing AgSbS2 solar cells is low and the open circuit voltage is insufficient, resulting in unsatisfactory efficiency.

Method used

A double-layer stacked sulfonyluoroante silver-based gradient film structure is adopted. The first layer is AgInxSb(S,Se)2 and the second layer is AgSb1+y(S,Se)2. A gradient energy band structure is formed by selenization treatment to improve light absorption and battery efficiency.

Benefits of technology

On the basis of retaining high short-circuit current, the open circuit voltage is increased, thereby significantly improving the efficiency of the solar cell and achieving a maximum power conversion efficiency of 3.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115966618B_ABST
    Figure CN115966618B_ABST
Patent Text Reader

Abstract

A double-layer stacked silver antimony sulfide-based gradient film, with silver antimony sulfide (AgSbS2) as the matrix and AgIn prepared by adding indium (In) x Sb(S,Se)2 is the first layer, antimony (Sb) is added to form AgSb 1+y (S, Se)2 is the second layer, where x = 0.1~0.5, y = 0.1~0.5. The double absorption layer gradient band gap AgIn in the present invention x Sb(S,Se)2 / AgSb 1+y The (S,Se)2 film has high purity, good crystallinity, large grain size, few defects such as holes and gaps, and the combination of the double absorption layer retains AgIn x The high short-circuit current of Sb(S,Se)2 thin film is based on the second layer of AgSb 1+y (S, Se)2 reduces the drop in open circuit voltage. Through the cooperation of double absorption layers, the efficiency of the entire solar cell is increased to a maximum of 3.5%. x Sb(S,Se)2 / AgSb 1+y ITO / CdS / AgIn with (S,Se)2 thin film as absorber 0.5 Sb(S,Se)2 / AgSb 1.25 (S,Se)2 / Au solar cells have excellent electrical performance, with Jsc reaching 17mA·cm ‑2 , Voc reaches 396.5mV and FF is 52.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic materials, and in particular to a double-layer stacked antimony-sulfur silver-based gradient film and a preparation method thereof. Background Art

[0002] Silver antimony sulfide (AgSbS2) is an antimony-based ternary sulfur compound material with a suitable band gap of 1.4-1.7 eV in near-infrared and visible light and an absorption coefficient of up to 10 in near-infrared and visible light. 4 -10 5 cm -1 , and the material is eco-friendly and non-toxic, making it a promising photovoltaic absorber. In recent years, new absorption layer materials represented by antimony sulfur have made great progress, but there is still a large gap compared with CdTe and CIGS. Some potential absorption layer materials such as Cu2SnS3, CuSbS2, CuSbSe2, and ZnSnN2 have also been studied and developed, but their efficiency is still lower than expected. Since AgSbS2 was used as a P-type absorption layer for the first time, there are currently few reports on AgSbS2 solar cells. PK Nair et al. reported a bandgap of 1.68 eV, but the grain size of the film was too small, which limited the photoconductivity of the film. Due to the low short-circuit current (JSC) of the device and almost no optoelectronic performance, JO Gonzales et al. subsequently discovered that the solution method for preparing AgSb(S x Se 1-x )2 film has good photoelectric properties. Based on AgSb(S x Se 1-x )2, the PCE is 2.7%, 9.70mAcm -2 However, it should be noted that despite the improvement in optoelectronic performance, the film preparation process is very complicated and time-consuming. Recently, Chengwu Shi et al. prepared a fully covered AgSbS2 film with close connection between grains and grain size increased to about 5 microns. The solar cell parameters are: Voc=440mV, Jsc=10.49mA / cm 2 , FF=0.45, =2.09%. Chen Tao et al. used spin coating and optimized heat treatment process to produce a solar cell with the structure of FTO / TiO2 / AgSbS2 / spiro-OMeTAD / Au, and the efficiency reached 2.25%. The microstructure of the AgSbS2 film was uniform, the grain shape was regular, and the size was about 3 microns. Its short-circuit current was greatly improved, resulting in an increase in the cell efficiency, which is currently the highest solar cell efficiency with AgSbS2 as the absorption layer. It can be seen that one of the ways to improve the electrical properties of pure AgSbS2 thin films is to optimize the preparation process, so that the film has a higher degree of crystallinity, a larger grain size, a uniform overall morphology, and fewer defects.

[0003] In recent years, we have used ultrasonic spray pyrolysis to prepare AgSbS2 thin films, which contain AgSbS2, AgSbSe2, and AgSb(SxSe1-x)2 after selenization heat treatment, to achieve a gradient band structure, greatly improving light absorption and increasing the efficiency of solar cell devices from 0.27% to 1.30%. CN113644146A uses In elements to prepare AgIn by direct addition. x Sb (2+3x / 2) (Se), ITO / CdS / AgIn x Sb (2+3x / 2) The efficiency of (Se) / Au solar cells is 1.98%, and the maximum short-circuit current can reach 20.65mA / cm2 (the maximum value reported so far), which is not far from the theoretical maximum short-circuit current. However, due to the reduction of its open-circuit voltage, the device efficiency has not been significantly improved.

[0004] Ultrasonic spray pyrolysis deposition (thermal spraying) is used to prepare AgSbS2 (Se) thin films. The operation is simple and the preparation efficiency is high. The spray liquid falls on the substrate at a certain speed, which is conducive to the preparation of multi-component thin films. However, the prepared films have many holes and gaps, the film grain size is small, and excessive selenization causes damage to the film structure, resulting in poor film performance. When applied to solar cells, the efficiency is still not ideal. Summary of the invention

[0005] The present invention aims to provide a double-layer stacked antimony sulfide silver-based gradient film, which improves the open circuit voltage while ensuring a high short-circuit current, thereby significantly improving the efficiency.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned film.

[0007] The third object of the present invention is to provide a solar cell using the above-mentioned double-layer stacked antimony sulfide silver-based gradient film as the absorption layer.

[0008] A fourth object of the present invention is to provide a method for preparing the above-mentioned solar cell.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A double-layer stacked antimony sulfide silver-based gradient film, characterized in that: the film is AgIn prepared by adding indium (In) to antimony sulfide silver (AgSbS2) as the matrix x Sb(S,Se)2 is the first layer, and AgSb prepared by adding antimony (Sb) 1+y (S,Se)2 is the second layer, where x=0.1~0.5, y=0.1~0.5.

[0011] Furthermore, preferably, the above x=0.5, y=0.25.

[0012] Furthermore, the double-layer stacked antimony-sulfur silver-based gradient film is prepared by spraying a spray liquid 1 using silver nitrate, indium nitrate, antimony acetate and thiourea as raw materials, and spraying and depositing AgIn x SbS2, as the first film, is prepared by spraying liquid 2 using silver nitrate, antimony acetate and thiourea. x AgSb deposited by spray coating on SbS2 surface 1+y S2, as the second film, is then selenized to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 bilayer stacked antimony sulfur silver-based gradient films.

[0013] Furthermore, the above-mentioned spray deposition is carried out at a N2 gas flow rate of 20-24L / min, a spray liquid feed rate of 0.3mL / min, a deposition temperature of 330°C, a deposition rate of 150nm / min, each deposition period of 2min is one cycle, and the first and second film layers are sprayed for 2 cycles each.

[0014] Furthermore, the spray liquid 1 is prepared by dissolving silver nitrate and indium nitrate in ethylene glycol methyl ether to form solution 1, dissolving antimony acetate in acetic acid to form solution 2, mixing solution 1 and solution 2, adding concentrated nitric acid with a mass concentration of 68%, and then adding acetic acid and thiourea to mix evenly.

[0015] Furthermore, the spray liquid 2 is prepared by dissolving silver nitrate in ethylene glycol methyl ether to form solution 3, dissolving antimony acetate in acetic acid to form solution 4, mixing solution 3 and solution 4, adding concentrated nitric acid with a mass concentration of 68%, and then adding acetic acid and thiourea to mix evenly.

[0016] A method for preparing a double-layer stacked sulfur antimony silver gradient film, characterized in that: a spraying liquid 1 is prepared using silver nitrate, indium nitrate, antimony acetate and thiourea as raw materials, and AgIn is sprayed and deposited. x SbS2, as the first film, is prepared by spraying liquid 2 using silver nitrate, antimony acetate and thiourea. x AgSb deposited by spray coating on SbS2 surface 1+y S2, as the second film, is then selenized to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 bilayer stacked antimony sulfur silver-based gradient films.

[0017] Furthermore, the above-mentioned spray deposition is carried out at a N2 gas flow rate of 20-24L / min, a spray liquid feed rate of 0.3mL / min, a deposition temperature of 330°C, a deposition rate of 150nm / min, each deposition period of 2min is one cycle, and the first and second film layers are sprayed for 2 cycles each.

[0018] Furthermore, the spray liquid 1 is prepared by dissolving silver nitrate and indium nitrate in ethylene glycol methyl ether to form solution 1, dissolving antimony acetate in acetic acid to form solution 2, mixing solution 1 and solution 2, adding concentrated nitric acid with a mass concentration of 68%, and then adding acetic acid and thiourea to mix evenly.

[0019] In the present invention, silver nitrate and indium nitrate are prepared into solution 1, antimony acetate is dissolved separately into solution 2 and then mixed to ensure that a precursor with In addition is generated, rather than a structure in which In replaces Sb. Finally, when thiourea is added, a small amount of acetic acid is also added to play a pH buffering role, which regulates the generation of the precursor in the spraying liquid, promotes a more uniform distribution of In, and improves the uniformity and density of the thin film deposited in the thermal spraying process.

[0020] Furthermore, in the spray liquid 1, the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol: 0.1-0.5 mmol: 13-15 mL.

[0021] Preferably, the molar volume ratio of the silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol:0.5 mmol:15 mL.

[0022] Furthermore, the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid in the spray liquid 1 is 1 mmol: 1 mmol: 4 mmol: 80 μL.

[0023] Furthermore, the spray liquid 2 is prepared by dissolving silver nitrate in ethylene glycol methyl ether to form solution 3, dissolving antimony acetate in acetic acid to form solution 4, mixing solution 3 and solution 4, adding concentrated nitric acid with a mass concentration of 68%, and then adding acetic acid and thiourea to mix evenly.

[0024] Furthermore, the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid in the spray liquid 2 is 1 mmol:1.1-1.5 mmol:4 mmol:80 μL.

[0025] Preferably, the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid in the spraying liquid 2 is 1 mmol:1.25 mmol:4 mmol:80 μL.

[0026] Furthermore, the molar volume concentration of antimony acetate in acetic acid in the above solution 2 and solution 4 is 0.29 mol / L.

[0027] Furthermore, the molar volume ratio of thiourea to acetic acid in the spray liquid 1 and the spray liquid 2 is 7.7-8 mmol:1 mL.

[0028] Furthermore, the selenization is to place the film in a high temperature zone of 380°C and the selenium powder in a low temperature zone of 350°C for 6 to 9 minutes to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

[0029] Preferably, the selenization time is 8 minutes.

[0030] Most specifically, a method for preparing a double-sided stacked antimony sulfide silver-based gradient film is characterized by following the steps:

[0031] 1. Preparation of spray liquid

[0032] (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol: 0.1-0.5 mmol: 13-15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea and acetic acid is 7.7-8 mmol: 1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol: 1 mmol: 4 mmol: 80 μL;

[0033] (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the molar volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea to acetic acid is 7.7~8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.1~1.5 mmol:4 mmol:80 μL;

[0034] (ii) Spray deposition film double layer film

[0035] (1) In a N2 environment, the N2 gas flow rate is 20~24L / min, and AgIn is deposited by ultrasonic spray pyrolysis. x SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃;

[0036] (2) Use spray liquid 2 on AgIn x SbS2 thin film was deposited under the same conditions as AgSb 1+y S2 film, forming a double-layer structure of AgIn x SbS2 / AgSb 1+y S2 film;

[0037] 3. Selenization

[0038] AgIn x SbS2 / AgSb 1+y The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 6~9min to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

[0039] Previous studies have found that adding indium and antimony at the same time can improve the crystallinity and phase purity of the film, and the addition of indium to silver antimony sulfide changes the band structure of silver antimony sulfide. The short-circuit current increases while the open-circuit voltage decreases, resulting in a small increase in efficiency. Therefore, the main problem with silver antimony sulfide-based materials as absorption layers is how to increase the open-circuit voltage while maintaining a high short-circuit current. Therefore, we designed a double absorption layer, both based on silver antimony sulfide. The silver antimony sulfide with added indium is the first layer to ensure a high short-circuit current, and the silver antimony sulfide with added antimony is the second layer to increase the open-circuit voltage.

[0040] Different from the general doping of chemical elements, in which the original structure remains unchanged as a whole, but only some elements at very small positions are replaced by doping elements, the indium element (In) and antimony element (Sb) in the double absorption layer of the present invention are directly added to the Ag-Sb-S-Se system. The elements are added into the lattice of AgSbS2 to form a multi-component compound. When anions are abundant (the proportion of thiourea is large), the atoms of the added elements enter the lattice to form a uniform compound on a macroscopic scale. The arrangement and thickness of the two absorption layers will affect the interface and the carrier movement in the film, changing the performance of the entire absorption layer. During the selenization process, In and Se compete for sites, and Se vapor heat diffuses from the surface of the absorption layer to the CdS layer to form a gradient distribution, which makes the energy level distribution of the double absorption layer present a gradient and causes the position of the element atoms to change, promoting the bonding of the double absorption layer interface. Since the added antimony and indium atoms change the strength of the chemical bonds in the lattice, Se is more strongly hindered than pure sulfur antimony silver when replacing S atoms, which inhibits the damage to the film performance caused by excessive Se vapor entering the lattice. For example, a large amount of Se diffuses into the film, resulting in the loss of Sb elements, an increase in film defects, and the generation of impurities.

[0041] A kind of AgIn x Sb(S,Se)2 / AgSb 1+y A solar cell with a (S, Se)2 double-layer stacked sulfur antimony silver-based gradient film as the absorption layer, characterized in that: the solar cell structure is ITO / CdS / AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 / Au.

[0042] The above AgIn x Sb(S,Se)2 / AgSb 1+y A method for preparing a solar cell with a (S, Se)2 double-layer stacked antimony sulfur silver-based gradient film as an absorption layer is characterized by the following steps:

[0043] S1 Cleaning ITO Substrate

[0044] Using ITO glass as the substrate, ultrasonic cleaning was performed with alkaline detergent and then ultrasonic cleaning with deionized water;

[0045] S2 deposits CdS buffer layer

[0046] A CdS buffer layer with a thickness of about 150 nm was deposited on the ITO substrate by chemical plating and then annealed at 400 °C for 5 min;

[0047] S3 Preparation of AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 Absorption Layer

[0048] 1. Preparation of spray liquid

[0049] (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol: 0.1-0.5 mmol: 13-15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea and acetic acid is 7.7-8 mmol: 1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol: 1 mmol: 4 mmol: 80 μL;

[0050] (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the mass volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea to acetic acid is 7.7~8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.1~1.5 mmol:4 mmol:80 μL;

[0051] (ii) Spray deposition film double layer film

[0052] (1) In a N2 environment, the N2 gas flow rate is 20~24L / min, and AgIn is deposited by ultrasonic spray pyrolysis. x SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃;

[0053] (2) Use spray liquid 2 on AgIn x SbS2 thin film was deposited under the same conditions as AgSb 1+y S2 film, forming a double-layer structure of AgIn x SbS2 / AgSb 1+y S2 film;

[0054] 3. Selenization

[0055] AgIn x SbS2 / AgSb 1+y The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 6~9min to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

[0056] S4 deposits Au electrode layer

[0057] Use ion sputtering coating machine to coat AgIn x Sb(S,Se)2 / AgSb 1+y A 60nm thick Au electrode layer was sputtered deposited on the surface of the (S,Se)2 absorption layer.

[0058] The present invention has the following technical effects:

[0059] The double absorption layer gradient band gap AgIn in the present invention x Sb(S,Se)2 / Sb1+y The (S,Se)2 film has high purity, good crystallinity, large grain size, few defects such as holes and gaps, and the combination of the double absorption layer retains AgIn x The high short-circuit current of Sb(S,Se)2 thin film is based on the second layer of AgSb 1+y (S, Se)2 reduces the drop in open circuit voltage. Through the cooperation of double absorption layers, the efficiency of the entire solar cell is increased to a maximum of 3.5%. 0.5 Sb(S,Se)2 / AgSb 1.25 (S,Se)2 / Au solar cells have excellent electrical performance, with Jsc reaching 17mA·cm -2 , Voc reaches 396.5mV, FF is 52.7%. The solar cells prepared with antimony sulfide silver-based materials as the absorption layer have the highest efficiency at present. This double absorption layer method has opened up new ideas for us to prepare higher efficiency solar cells in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 :AgIn with different spraying cycles 0.5 Sb(S,Se)2 / AgSb 1.25 XRD pattern of (S,Se)2 thin film.

[0061] Figure 2 :AgIn with different spraying cycles 0.5 Sb(S,Se)2 / AgSb 1.25 EQE curve of (S,Se)2 film.

[0062] Figure 3 :AgIn prepared by different spraying cycles 0.5 Sb(S,Se)2 / AgSb 1.25 Optical absorption spectrum of (S,Se)2 thin film.

[0063] Figure 4 :AgIn with different spraying cycles 0.5 Sb(S,Se)2 / AgSb 1.25 Cross-sectional SEM image of (S,Se)2 film.

[0064] Figure 5 :AgIn with different spraying cycles 0.5 Sb(S,Se)2 / AgSb 1.25 Surface SEM image of (S,Se)2 film.

[0065] Figure 6 : JV curves of solar cells with absorber layers prepared with different spraying cycles.

[0066] Figure 7 :AgIn prepared with different selenization times 0.5 Sb(S,Se)2 / AgSb 1.25 JV curve of the solar cell corresponding to the (S,Se)2 absorber layer. DETAILED DESCRIPTION

[0067] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0068] Example 1

[0069] A method for preparing a double-sided stacked antimony sulfide silver-based gradient film is carried out according to the following steps:

[0070] 1. Preparation of spray liquid

[0071] (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol:0.25 mmol:13 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea and acetic acid is 7.7 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1 mmol:4 mmol:80 μL;

[0072] (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the mass volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea to acetic acid is 7.7 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.1 mmol:4 mmol:80 μL;

[0073] (ii) Spray deposition film double layer film

[0074] (1) In a N2 environment, the N2 gas flow rate is 20L / min, and AgIn is deposited by ultrasonic spray pyrolysis. 0.25SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃;

[0075] (2) Use spray liquid 2 on AgIn 0.25 SbS2 thin film was deposited under the same conditions as AgSb 1.1 S2 film, forming a double-layer structure of AgIn 0.25 SbS2 / AgSb 1.1 S2 film;

[0076] 3. Selenization

[0077] AgIn 0.25 SbS2 / AgSb 1.1 The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 9 minutes to form AgIn 0.25 Sb(S,Se)2 / AgSb 1.1 (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

[0078] Example 2

[0079] A method for preparing a double-sided stacked antimony sulfide silver-based gradient film is carried out according to the following steps:

[0080] 1. Preparation of spray liquid

[0081] (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol:0.4 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea and acetic acid is 8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1 mmol:4 mmol:80 μL;

[0082] (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the mass volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume ratio of antimony acetate to acetic acid is 1 mmol:4 mL, the molar volume ratio of thiourea to acetic acid is 8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.2 mmol:4 mmol:80 μL;

[0083] (ii) Spray deposition film double layer film

[0084] (1) In a N2 environment, the N2 gas flow rate was 22 L / min, and AgIn was deposited by ultrasonic spray pyrolysis. 0.4 SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃;

[0085] (2) Use spray liquid 2 on AgIn 0.4 SbS2 thin film was deposited under the same conditions as AgSb 1.2 S2 film, forming a double-layer structure of AgIn 0.4 SbS2 / AgSb 1.2 S2 film;

[0086] 3. Selenization

[0087] AgIn 0.4 SbS2 / AgSb 1.2 The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 6 minutes to form AgIn 0.4 Sb(S,Se)2 / AgSb 1.2 (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

[0088] Example 3

[0089] A method for preparing a double-sided stacked antimony sulfide silver-based gradient film is carried out according to the following steps:

[0090] 1. Preparation of spray liquid

[0091] (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1mmol:0.5mmol:15mL, the molar volume concentration of antimony acetate in acetic acid is 0.29mol / L, the molar volume ratio of thiourea and acetic acid is 8mmol:1mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1mmol:1mmol:4mmol:80μL;

[0092] (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the mass volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea to acetic acid is 8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.25 mmol:4 mmol:80 μL;

[0093] (ii) Spray deposition film double layer film

[0094] (1) In a N2 environment, the N2 gas flow rate was 24 L / min, and AgIn was deposited by ultrasonic spray pyrolysis. 0.5 SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃;

[0095] (2) Use spray liquid 2 on AgIn 0.5 SbS2 thin film was deposited under the same conditions as AgSb 1.25 S2 film, forming a double-layer structure of AgIn 0.5 SbS2 / AgSb 1.25 S2 film;

[0096] 3. Selenization

[0097] AgIn 0.5 SbS2 / AgSb 1.25 The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 8 minutes to form AgIn 0.5 Sb(S,Se)2 / AgSb 1.25 (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

[0098] Comparative Example 1:

[0099] The difference from Example 3 is that by changing AgIn 0.5 SbS2 thin film and AgSb 1.25 The spraying cycle of S2 film is used to prepare 4 cycles of AgIn 0.5 SbS2 single layer film, 1 cycle AgIn 0.5 SbS2+3 period AgSb 1.25 S2 double-layer film, 3-cycle AgIn 0.5 SbS2+1 cycle AgSb 1.25 S2 double-layer film and 4-period AgSb 1.25 S2 single-layer film.

[0100] Figure 1 AgIn prepared in different cycles 0.5 Sb(S,Se)2 / AgSb 1.25 From the XRD diagram of the (S,Se)2 film, it can be seen that the double absorption layer is relatively uniform after selenization, and the crystal form is between AgSbS2 and AgSbSe2, which is a solid solution of the two, AgSb(S,Se)2. The added indium or antimony atoms do not generate detectable second phases or impurities, indicating that the atoms of the two elements have entered the AgSb(S,Se)2 lattice to form a uniform phase. However, during the selenization process, in the longitudinal direction, due to the difference in the concentration and diffusion rate of selenium that the film layer contacts, the diffusion of selenium atoms in the longitudinal direction of the film is gradient distributed, which also affects the distribution of atoms of other elements, such as Sb, S and In. The interface of the double absorption layer in the longitudinal direction is not obvious. Due to the thermal diffusion effect during selenization, the band gap of the entire film is gradient distributed in the longitudinal direction, which promotes the movement of carriers. For comparison, the four periods of AgIn 0.5 Sb(S,Se)2 single layer film and AgSb 1.25 However, the XRD pattern of the (S,Se)2 single-layer film shows impure phases, indicating that the phase purity is not high. It may be divided into two phases of AgSbS2 and AgSbSe2 and other compounds, which reduces the performance of the solar cell.

[0101] from Figure 2 It can be clearly seen that AgIn 0.5 Sb(S,Se)2 / AgSb 1.25 (S,Se)2 thin film with 2-period AgIn 0.5 Sb(S,Se)2+2 period AgSb 1.25 The EQE value of the double-layer film composed of (S,Se)2 is the highest, reaching more than 70%, while the single 4-period AgSb 1.25 (S,Se)2 single-layer film has the lowest EQE, followed by 4-period AgIn0.5 Sb(S,Se)2 monolayer film. Transmission spectroscopy Figure 3 It can be seen that as the absorption layer of the double-layer stack, the 2-period AgIn 0.5 SbS2+2 period AgSb 1.25 The absorption layer composed of S2 absorbs the most, and can absorb wavelengths up to 1200nm, near-infrared region. Better light absorption improves its efficiency.

[0102] Figure 4 Among them, (a) is 4-period AgSb 1.25 (S,Se)2 single layer film, (b) is 1 period AgIn 0.5 Sb(S,Se)2+3 period AgSb 1.25 (S,Se)2 double-layer film, (c) 2-period AgIn 0.5 Sb(S,Se)2+2 period AgSb 1.25 (S,Se)2 double-layer film, (d) is 3-period AgIn 0.5 Sb(S,Se)2+1 period AgSb 1.25 (S,Se)2 double-layer film; (e) 4-period AgIn 0.5 Sb(S,Se)2 single-layer film; (b) it can be clearly seen that the first layer of AgIn 0.5 Sb(S,Se)2 and the second layer AgSb 1.25 The (S,Se)2 film has a different profile, but because it is the same system, the spraying speed is fast, and the subsequent selenization heat treatment atoms diffuse again, the two layers are very tightly combined, and there is no obvious interface, so there is no big obstacle in the carrier transmission, and the short-circuit current of the device is not much lost. The first layer of AgIn 0.5 Sb(S,Se)2 is in contact with CdS, which has a more suitable band structure and a smaller crystal material. As can be seen from Figure (e), its grains are longer in the horizontal direction, with a lamellar stacking trend and good density. The second layer of AgSb 0.5 (S,Se)2 grains are larger and tend to be longer in the longitudinal direction, but not as good as AgIn 0.5 Sb(S,Se)2 dense, (c) 2 periodic AgIn 0.5 Sb(S,Se)2+2 period AgSb 1.25 The (S,Se)2 device has the highest efficiency, and its cross-section appears to be well crystalline and tightly bonded.

[0103] Figure 5 Among them, (a) is 4-period AgSb 1.25 (S,Se)2 single layer film; (b) 1 period AgIn 0.5Sb(S,Se)2+3 period AgSb 1.25 (S, Se)2 double-layer film; (c) 2-period AgIn 0.5 Sb(S,Se)2+2 period AgSb 1.25 (S, Se)2 double-layer film; (d) 3-period AgIn 0.5 Sb(S,Se)2+1 period AgSb 1.25 (S,Se)2 double-layer film; (e) 4-period AgIn 0.5 Sb(S,Se)2 single layer film; (e) is AgIn 0.5 Sb(S,Se)2 surface image, the rest are AgSb 1.25 (S,Se)2, because the top layer is AgSb 1.25 The (S,Se)2 films, with different thicknesses, show different morphologies after selenization, but are generally loose, and the grains on the top tend to dissolve, forming a network-like structure. From the cross-sectional view, it can be seen that longitudinal growth may form this morphology on the surface.

[0104] Example 4

[0105] A kind of AgIn x Sb(S,Se)2 / AgSb 1+y (S, Se)2 double-layer stacked sulfur antimony silver-based gradient film as an absorption layer of the solar cell, the solar cell structure is ITO / CdS / AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 / Au.

[0106] The above AgIn x Sb(S,Se)2 / AgSb 1+y The preparation method of a solar cell with a (S, Se)2 double-layer stacked antimony sulfur silver-based gradient film as an absorption layer is carried out according to the following steps:

[0107] S1 Cleaning ITO Substrate

[0108] Using ITO glass as the substrate, ultrasonic cleaning was performed with alkaline detergent and then ultrasonic cleaning with deionized water;

[0109] S2 deposits CdS buffer layer

[0110] A CdS buffer layer with a thickness of about 150 nm was deposited on the ITO substrate by chemical plating and then annealed at 400 °C for 5 min;

[0111] S3 Preparation of AgIn x Sb(S,Se)2 / AgSb 1+y(S,Se)2 Absorption Layer

[0112] Prepare AgIn according to the method of Example 3 0.5 Sb(S,Se)2 / AgSb 1.25 (S,Se)2 absorption layer;

[0113] S4 deposits Au electrode layer

[0114] Use ion sputtering coating machine to coat AgIn x Sb(S,Se)2 / AgSb 1+y A 60nm thick Au electrode layer was sputtered deposited on the surface of the (S,Se)2 absorption layer.

[0115] Comparative Example 2

[0116] The difference from Example 4 is that AgIn 0.5 Sb(S,Se)2 / AgSb 1.25 The (S, Se)2 absorption layer was prepared by the same spraying cycle as in Comparative Example 1 for 4 cycles of AgIn 0.5 Sb(S,Se)2 single-layer thin film absorption layer, 1 period AgIn 0.5 Sb(S,Se)2+3 period AgSb 1.25 (S,Se)2 double absorption layer, 3-period AgIn 0.5 Sb(S,Se)2+1 period AgSb 1.25 (S,Se)2 double absorption layer and 4-period AgSb 1.25 Solar cell corresponding to the (S,Se)2 single absorber layer.

[0117] The performance parameters of solar cells using thin films prepared at different times as the absorption layer are shown in Table 1.

[0118] Table 1:

[0119]

[0120] from Figure 6 The JV curve shows that AgIn prepared with different spraying cycles 0.5 Sb(S,Se)2 / AgSb 1.25 In the JV curve of the solar cell with (S,Se)2 thin film as the absorber layer, the AgIn 0.5 AgSb of Sb(S,Se)2+2 period 1.25 The absorption layer composed of (S, Se)2 has the best performance. The performance of the film in the solar cell can be adjusted by forming a gradient change through selenization.

[0121] In previous studies, a single 2T periodic AgSb1.25 In solar cells with S2 thin film as the absorption layer, the short-circuit current Voc is significantly improved compared with that of solar cells with AgSbS2 thin film as the absorption layer, which also improves PCE to a certain extent; due to its large Voc improvement and large band gap, theoretically, AgSbS2 should be deposited on the CdS surface first. 1.25 S2 film has better performance. Therefore, during the preparation process, we tried to prepare AgSb on the CdS surface first. 1.25 S2 is used as the first film, and then AgIn is prepared 0.5 SbS2 was used as the second film, but the performance of the prepared solar cells was found to be extremely poor, with serious attenuation of short-circuit current and current density. 1.25 The energy band difference between S2 film and CdS is large, and the interface bonding is also poor, similar to the above 4-period AgSb 1.25 (S,Se)2 single absorber layer solar cell. Since the conduction band offset (CBO) between the AgSbS2-based absorber layer and the N-type buffer layer is an important factor limiting the photoelectric conversion efficiency of AgSbS2-based thin-film solar cells, the band structure at the interface can be divided into two types: when the conduction band bottom of the P-type absorber layer is higher than the N-type buffer layer, it is a cliff type. At this time, the carrier recombination probability at the heterojunction interface will increase, resulting in the V oc When the conduction band bottom of the P-type absorption layer is lower than that of the N-type buffer layer, it is a spike type. At this time, an electronic barrier will be formed at the heterojunction interface. If the barrier height is too large, the photocurrent will be greatly reduced. For AgSbS2 thin-film solar cells, the N-type buffer layer mostly uses a CdS buffer layer. The conduction band position of AgSbS2 is about 0.95eV higher than that of CdS. The higher the CBO, the worse the efficiency of the device. After adding indium, silver antimony sulfide greatly reduces the CBO to 0.16, making the energy band matching at the pn interface more suitable. This indicates that the carrier recombination rate at the interface is low, resulting in a higher carrier transfer efficiency.

[0122] Example 5

[0123] Compared with Example 4, the difference is that the double-layer AgIn x SbS2 / AgSb 1+y When the S2 film is selenized, the selenization time is changed to 6 min, 7 min, 9 min and 10 min, and the remaining steps are the same as those in Example 4.

[0124] from Figure 7 It can be seen that when selenization is performed for 8 minutes, the corresponding film performance is the best.

Claims

1. A double-layer stacked antimony sulfide silver-based gradient film, characterized in that: The film is AgIn prepared by adding indium (In) with silver antimony sulfide (AgSbS2) as the matrix. x Sb(S,Se)2 is the first layer, antimony (Sb) is added to form AgSb 1+y (S,Se)2 is the second layer, where x=0.1~0.5, y=0.1~0.

5.

2. A method for preparing a double-layer stacked antimony sulfur silver gradient film as claimed in claim 1, characterized in that: The spraying liquid 1 is prepared by using silver nitrate, indium nitrate, antimony acetate and thiourea as raw materials, and AgIn is sprayed and deposited. x SbS2, as the first film, is prepared by spraying liquid 2 using silver nitrate, antimony acetate and thiourea. x AgSb deposited by spray coating on SbS2 surface 1+y S2, as the second film, forms AgIn x SbS2 / AgSb 1+y S2 double-layer film, and then selenized to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 bilayer stacked antimony sulfur silver-based gradient films.

3. The method for preparing a double-layer stacked antimony sulfur silver gradient film according to claim 2, characterized in that: The spray deposition is carried out at a N2 gas flow rate of 20-24 L / min, a spray liquid feed rate of 0.3 mL / min, a deposition temperature of 330°C, a deposition rate of 150 nm / min, and one deposition cycle of 2 minutes. The first and second thin film layers are sprayed for 2 cycles each.

4. A method for preparing a double-layer stacked antimony sulfur silver gradient film according to claim 2 or 3, characterized in that: The spraying liquid 1 is prepared by dissolving silver nitrate and indium nitrate in ethylene glycol methyl ether to form solution 1, dissolving antimony acetate in acetic acid to form solution 2, mixing solution 1 and solution 2, adding concentrated nitric acid with a mass concentration of 68%, and then adding acetic acid and thiourea to mix evenly.

5. The method for preparing a double-layer stacked antimony sulfur silver gradient film according to claim 4, characterized in that: In the spray liquid 1, the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1mmol:0.1-0.5mmol:13-15mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1mmol:1mmol:4mmol:80μL.

6. The method for preparing a double-layer stacked antimony sulfur silver gradient film according to claim 5, characterized in that: The spraying liquid 2 is prepared by dissolving silver nitrate in ethylene glycol methyl ether to form solution 3, dissolving antimony acetate in acetic acid to form solution 4, mixing solution 3 and solution 4, adding concentrated nitric acid with a mass concentration of 68%, and then adding acetic acid and thiourea to mix evenly.

7. The method for preparing a double-layer stacked antimony sulfur silver gradient film according to claim 6, characterized in that: The molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid in the spray liquid 2 is 1 mmol:1.1-1.5 mmol:4 mmol:80 μL.

8. A method for preparing a double-sided stacked antimony sulfide silver-based gradient film, characterized in that: Proceed as follows:

1. Preparation of spray liquid (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1mmol:0.1-0.5mmol:13-15mL, the molar volume concentration of antimony acetate in acetic acid is 0.29mol / L, the molar volume ratio of thiourea and acetic acid is 7.7-8mmol:1mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1mmol:1mmol:4mmol:80μL; (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the mass volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea to acetic acid is 7.7~8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.1~1.5 mmol:4 mmol:80 μL; (ii) Spray deposition film double layer film (1) In a N2 environment, the N2 gas flow rate is 20~24L / min, and AgIn is deposited by ultrasonic spray pyrolysis. x SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃; (2) Use spray liquid 2 on AgIn x SbS2 thin film was deposited under the same conditions as AgSb 1+y S2 film, forming a double-layer structure of AgIn x SbS2 / AgSb 1+y S2 film; 3. Selenization AgIn x SbS2 / AgSb 1+y The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 6~9min to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 double-layer stacking of antimony-sulfur silver-based gradient films.

9. AgIn prepared by the method of claim 8 x Sb(S,Se)2 / AgSb 1+y A solar cell with a (S, Se)2 double-layer stacked antimony sulfur silver-based gradient film as an absorption layer, characterized in that: The solar cell structure is ITO / CdS / AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 / Au.

10. The AgIn as claimed in claim 9 x Sb(S,Se)2 / AgSb 1+y A method for preparing a solar cell with a (S, Se)2 double-layer stacked antimony sulfur silver-based gradient film as an absorption layer, characterized in that: Proceed as follows: S1 Cleaning ITO Substrate Using ITO glass as the substrate, ultrasonic cleaning was performed with alkaline detergent and then ultrasonic cleaning with deionized water; S2 deposits CdS buffer layer A 150 nm thick CdS buffer layer was deposited on the ITO substrate by chemical plating and then annealed at 400 °C for 5 min; S3 Preparation of AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 Absorption Layer 1. Preparation of spray liquid (1) Silver nitrate and indium nitrate are dissolved in ethylene glycol methyl ether to form a mixed solution 1, antimony acetate is dissolved in acetic acid to form a mixed solution 2, solution 1 and solution 2 are mixed, concentrated sulfuric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 1, wherein the molar volume ratio of silver nitrate, indium nitrate and ethylene glycol methyl ether is 1 mmol: 0.1-0.5 mmol: 13-15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea and acetic acid is 7.7-8 mmol: 1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol: 1 mmol: 4 mmol: 80 μL; (2) Silver nitrate is dissolved in ethylene glycol methyl ether to form a mixed solution 3, antimony acetate is dissolved in acetic acid to form a mixed solution 2, the mixed solution 3 and the mixed solution 4 are mixed, concentrated nitric acid with a mass concentration of 68% is added, and finally acetic acid and thiourea are added to form a spray solution 2, wherein the molar volume ratio of silver nitrate to ethylene glycol methyl ether is 1 mmol:15 mL, the molar volume concentration of antimony acetate in acetic acid is 0.29 mol / L, the molar volume ratio of thiourea to acetic acid is 7.7~8 mmol:1 mL, and the molar volume ratio of silver nitrate, antimony acetate, thiourea and concentrated nitric acid is 1 mmol:1.1~1.5 mmol:4 mmol:80 μL; (ii) Spray deposition film double layer film (1) In a N2 environment, the N2 gas flow rate is 20~24L / min, and AgIn is deposited by ultrasonic spray pyrolysis. x SbS2 film, the feed rate of spray liquid 1 is 0.3mL / min, the deposition rate is 150nm / min, each cycle is 2min, 2 cycles are deposited, and the deposition temperature is 330℃; (2) Use spray liquid 2 on AgIn x SbS2 thin film was deposited under the same conditions as AgSb 1+y S2 film, forming a double-layer structure of AgIn x SbS2 / AgSb 1+y S2 film; 3. Selenization AgIn x SbS2 / AgSb 1+y The S2 film was placed in the 380℃ high temperature zone of the heat treatment furnace, and the selenium powder was placed in the 350℃ low temperature zone for selenization for 6~9min to form AgIn x Sb(S,Se)2 / AgSb 1+y (S,Se)2 double-layer stacking stacked antimony sulfur silver-based gradient films; S4 deposits Au electrode layer Use ion sputtering coating machine to coat AgIn x Sb(S,Se)2 / AgSb 1+y A 60nm thick Au electrode layer was sputtered deposited on the surface of the (S,Se)2 absorption layer.

Citation Information

Patent Citations

  • Thin film for solar cell, solar cell and preparation method thereof

    CN113644146A